A divergent route to core- and peripherally functionalized diazacoronenes that act as colorimetric and fluorescence proton sensors1. Issue 5 (20th May 2015) - He, Bo; Dai, Jing; Zherebetskyy, Danylo; Chen, Teresa L.; Zhang, Benjamin A.; Teat, Simon J.; Zhang, Qichun; Wang, Linwang; Liu, Yi
<x xml:space="preserve">Abstract</x> One-stop center for functional polycyclic aromatic hydrocarbons — a dichlorodiazaperylene intermediate has been synthesized and employed for the synthesis of highly functionalized coronene derivatives.